2010
DOI: 10.1007/s00701-010-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography, digital subtraction angiography and Doppler ultrasonography in detection of carotid artery stenosis: a comparison with findings from histological specimens

Abstract: Our study confirms that DSA underestimates moderate and mild ICA stenosis. DUS slightly overestimated moderate ICA stenosis and highly overestimated high-grade ICA stenosis. MRA proved to be accurate in detecting moderate ICA stenosis, but slightly underestimated mild stenosis and overestimated high-grade stenosis. The surgeon should be aware of these discrepancies when deciding whether to perform CEA in patients with ICA stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previous results have indicated that CDUS evaluations generally overestimate the degree of stenosis (23). In the current study, some false-positive results were generated by CDUS, possibly due to differences in the imaging principles for CDUS and DSA.…”
Section: Degree Of Degree Of Stenosis By Dsa Stenosis ---------------mentioning
confidence: 47%
“…Previous results have indicated that CDUS evaluations generally overestimate the degree of stenosis (23). In the current study, some false-positive results were generated by CDUS, possibly due to differences in the imaging principles for CDUS and DSA.…”
Section: Degree Of Degree Of Stenosis By Dsa Stenosis ---------------mentioning
confidence: 47%
“…Recent literature and the current study, however, suggest that DSA may incorrectly estimate true stenosis when its findings are compared with those of other imaging modalities as well as measurements in histological specimens. 5,17,26 Although these studies were conducted in the extracranial carotid artery, this body of evidence raises a question about the validity of what is considered our gold standard. DSA may not provide an optimal assessment of plaque stenosis and morphology in ICAD.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 103 patients undergoing endarterectomy had their plaque sectioned transversally and assessed planimetrically. 13 All patients had preoperative catheter angiography and MRA. Overall, catheter angiography underestimated histological stenosis by 14.5%, whereas MRA underestimated histological stenosis by only 0.7%.…”
Section: Identifying and Characterizing Carotid Stenosismentioning
confidence: 99%